The Big Five: Pro et contra - Kairys, Antanas (Psichologija, 2008)
The field of the personality research is very active these days; probably more research is being conducted than ever. Most of the research studies are conducted referring to the Big Five model. Nevertheless, this model is controversial. Some researchers emphasize the merits of the Big Five model and the others name the shortcomings of the model. The main merits of the Big Five model are: empirical validity, cross-cultural validity, stability of individual differences and practical model value. Still the Big Five model receives criticism. The main critiques are: discussions about lexical hypothesis, orthogonality of factors, problems in cross – cultural research and prognostic value of the Big Five model. Despite the debates, nonetheless, the strongest arguments are for Big Five model. There is more empirical evidence still difficulties arise because of the research procedure or method inaccuracy. Most of the researchers confirmed that it is complicated to extract less than five factors in many research data. Five factors is the optimal number. There also have been determined many associations between Big Five traits and other mental / psychological phenomena. For a long time Big Five was only the research model, but presently initial theoretical interpretations were offered – R. R. McCrae and P. T. Costa Five Factor Theory also D. P. McAdams and J. L. Pals New Big Five. This was a substantial sally – Big Five has a potential to become the real personality theory, but there are still some problems left unsolved – extracted factor relevance to the individual in large samples is unclear, newly posed statements about personality structure lack empirical evidence. Alternative models to the Big Five model are offered: Biggest One, Big Two, Giant Three, HEXACO and Big Seven. Presently alternative models are not in competition with Big Five. Perhaps more promising is a HEXACO model with its theoretical interpretations. Alternative models to Big Five model play another important role – they encourage cross-cultural research, the search of the neurological correlates. Thus Big Five is very dynamic field of personality research, pretending to become very important and influential personality theory. Herewith it is obvious: there is an essential challenge against Big Five model– whether it will become one or not? Establishing Big Five or other close models’ theoretical interpretations give hope, but the final result is still to be expected.
Keywords: personality traits; Five Factor Model; Big Five